Environmental factors driving seed dormancy and germination in tropical ecosystems: A perspective from campo rupestre species - Garcia, Queila S.; Barreto, Leilane C.; Bicalho, Elisa M. (Environmental and experimental botany, 2020)
•Germination temperature thresholds are related to moisture in the microhabitats.•ABA mediates interactions between light and temperature to germinate.•Most species from campo rupestre can form long-term persistent soil seed banks.•Cyclical dormancy is highly synchronized with the soil moisture seasonality.•Induction of secondary dormancy is related to low GA levels rather than high ABA. Campo rupestre is a mountain tropical landscape occurring in Brazil. It is considered one of the most biologically diverse ecosystems in the world and a major center of endemism. This review addresses the particularities and crucial roles that environmental signaling plays in germination, longevity, and dormancy cycles of seeds of tropical species from campo rupestre vegetation. It also addresses how microhabitats can influence the hormonal and biochemical control of seed germination, longevity and dormancy, as well as how the interaction between soil humidity and temperature can modulate the acquisition and overcoming of secondary dormancy, affecting dormancy cycles of important groups of campo rupestre species. The available data show that most species of campo rupestre produce small seeds that germinate in a wide range of temperatures, require light to germinate and are able to form long-term persistent soil seed banks. Special attention should be given to seeds of Velloziaceae, which germinate in the dark at high temperatures with germination mediated mainly by abscisic acid, and to seeds of Eriocaulaceae and Xyridaceae, which have cyclical dormancy in fine synchrony with the seasonality of campo rupestre. Seasonal water availability, along with temperature, has shown to play a critical role in annual dormancy cycles, with the dynamics of gibberellins and abscisic acid levels driving the acquisition of secondary dormancy. This information is essential for understanding interactions between seeds and the environment and will provide useful contributions to the conservation and maintenance of campo rupestre vegetation and the preservation of this unique ecosystem.